294 Incidence trends and long-term outcomes of juvenile myocardial infarction: does gender matter?. (8th December 2021) - Bruno, Francesco; Moirano, Giovenale; Budano, Carlo; Lalloni, Stefania; Ciccone, Giovannino; Verardi, Roberto; Andreis, Alessandro; Montabone, Andrea; Gilardetti, Marco; De Filippo, Ovidio; D'Ascenzo, Fabrizio; De Ferrari, Gaetano Maria
Abstract: Aims: Data about long-term clinical outcomes of young patients experiencing an acute myocardial infarction (MI), along with the potential impact of gender on incidence and prognosis in such subset are scant and mostly including USA populations. Thus, there is a paucity of data about European patients suffering from a juvenile MI. Purpose. The purpose of the current study was to investigate temporal trends, survival, MI recurrence, and sex differences among subjects who experienced their first MI at young age in the Piedmont region (Italy) between 2007 and 2018. Methods and results: Hospital Discharge Register records of Piedmont region (Italy) from 2007 to 2018 were interrogated to identify incident juvenile MI cases and MI recurrences (ICD-9-CM codes: '410', '411', and their subcodes). Patients were considered young if the first MI occurred before or at 47 years of age. Incidence of first Juvenile MI event and subsequent overall survival among patients who survived to hospital discharge were defined as primary outcomes of interest. Subgroup analysis were performed according to sex category, comorbidities and clinical intervention (obtained from the HDRs records). Incidence of MI recurrence among patients who survived to hospital discharge was defined as secondary outcome of interest. Lastly, we evaluated whether experiencing a MI recurrence was associated with a lower overall survival at follow-up. Out of 114 816 hospitalizations due to MI, 4482 occurred in people aged ≤47, with median age 44 years old. At baseline, men had more hypertension (13% vs. 9.4%, P < 0.006) and dyslipidaemia (18.2% vs. 9.9%, P < 0.001), while women more cardiac arrest at presentation (2.9% vs. 1.7%, P = 0.03), cardiogenic shock (2.1% vs. 1.3%, P = 0.06), and less likely to undergone PCI (53.9% vs. 74.3%, P < 0.001). More women (n = 14; 1.9%) than men (n = 33; 0.9%) died while in-hospital, adjusted OR: 2.12; 1.13–3.99. After a median follow-up was 7.2 years (IQR: 4.2–9.9), the survival rate after the first MI was 94.8%, without differences between men and women (HR: 1.05; 0.69–1.60). Age at first MI, year of hospitalization, hospitalization length, chronic kidney disease, cardiogenic shock, third degree atrio-ventricular block, and PCI were found independent predictors of long term survival. 348 (7.8%) experienced at least one MI recurrence and it was more common in men than women (adjusted HR: 0.72; 0.52–0.99). After multivariate adjustment, MI recurrence was associated with a significantly higher risk of death at follow-up as compared with a single MI episode (HR: 3.05; 1.9–4.80, all 95% CI). Conclusions: In young patients with a MI, women had more in-hospital mortality compared to men, but among patients who survived to hospital discharge, overall long-term prognosis did not differ. MI recurrences were more common in men and were associated with lower long-term survival rate.